2001
DOI: 10.1080/10715760100300011
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of folic acid against oxidative stress produced in 21-day postpartum rats by maternal-ethanol chronic consumption during pregnancy and lactation period

Abstract: In this paper we show the protective effect of folic acid on oxidative stress in offspring caused by chronic maternal ethanol consumption during pregnancy and the lactation period. Glutathione reductase (GR) specific activity was assayed in liver and pancreas of offspring and mothers. In the offspring, these tissues were also assayed for markers of oxidative damage to lipids and proteins. The results show that ethanol exposure during pregnancy and lactation increased the specific activity of GR in tissues of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
54
1
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(59 citation statements)
references
References 42 publications
3
54
1
1
Order By: Relevance
“…The current study provides in vivo evidence for the antioxidative activity of folate and FDH. Our results also support the beneficial effects of folate supplementation to developing embryos, especially for those at risk of FAS (28,29). By overexpressing and knocking down fdh, we observed that the embryonic THF level was modulated by the FDH level.…”
Section: Discussionsupporting
confidence: 68%
“…The current study provides in vivo evidence for the antioxidative activity of folate and FDH. Our results also support the beneficial effects of folate supplementation to developing embryos, especially for those at risk of FAS (28,29). By overexpressing and knocking down fdh, we observed that the embryonic THF level was modulated by the FDH level.…”
Section: Discussionsupporting
confidence: 68%
“…The exact mechanisms remain unknown, but the addition of the free radical scavenging enzyme superoxide dismutase has been shown to significantly reverse the effects of ethanol in vitro [Amini et al, 2009;Davis et al, 1990]. Using antioxidants, these anomalies have been partially reversed in vivo, implying that oxidative stress plays a partial role in their development [Cano et al, 2001;Peng et al, 2005;Reimers et al, 2006].…”
Section: Alcohol As a Teratogenmentioning
confidence: 99%
“…This is in agreement with previous results indicating the anti-lipid peroxidation properties of folic acid. 18) Although 1 mM of THF acid only partially prevented the formation of LP, induction of oxidative damage to lipids was totally prevented by 25 mM THF.…”
Section: )mentioning
confidence: 99%